1980
DOI: 10.1159/000131415
|View full text |Cite
|
Sign up to set email alerts
|

An examination of chromosomes in the stallion (<i>Equus caballus</i>) during meiosis

Abstract: Meiotic preparations were made from testicular material obtained after surgical castration of eight stallions (Equus caballus) with normal spermatogenesis. The material was examined after conventional Giemsa staining and C-banding. C-banding demonstrated that the Y chromosome at diakinesis associated with the short arm of the X chromosome. In 315 cells at diplotene or diakinesis, 56 (17.7%) had univalents and 51 (16.1%) of these involved the sex chromosomes. The overall mean chiasma number was 54.4 ± 1.8 sd, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 10 publications
(13 reference statements)
3
5
1
Order By: Relevance
“…Our results are consistent with previous studies indicating the terminal associations between the distal segment of the acrocentric Y and the short arm of the submetacentric X chromosome to form the pseudoautosomal region in the horse (Scott and Long 1980; Power et al 1992). However, our study provides critical insight into the frequency and chromosomal distribution of recombination events in the equine species.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Our results are consistent with previous studies indicating the terminal associations between the distal segment of the acrocentric Y and the short arm of the submetacentric X chromosome to form the pseudoautosomal region in the horse (Scott and Long 1980; Power et al 1992). However, our study provides critical insight into the frequency and chromosomal distribution of recombination events in the equine species.…”
Section: Discussionsupporting
confidence: 94%
“…Pioneering studies used air-dried chromosomal spreads to describe the meiotic chromosomes of equine interspecific hybrids as well as the number of chiasmata during normal meiosis in the stallion (Chandley et al 1974; Scott and Long 1980). A subsequent study used electron microscopy for the analysis of synaptic abnormalities in a horse carrying an autosomal trisomy (Power et al 1992).…”
Section: Discussionmentioning
confidence: 99%
“…In male horses the mean frequency of chiasmata per nucleus reported in this study was 50.45 ± 2.07, which is less than reported by Scott and Long [1980] (54.40 ± 1.80 per cell). These differences could be attributed to several factors, such as different stallions, methodology, and research groups.…”
Section: Chiasmata Frequency and Distribution In All Chromosomescontrasting
confidence: 82%
“…In at least some species the male recombination rate is considerably less than that in females (Morton 1991;Ellegren et al 1994), but this might not be a ubiquitous phenomenon among mammals as suggested by data for cattle and sheep (Crawford et al 1995;Barendse et al 1997). The only clue to the genetic length of the equine genome comes from the analysis of meiotic chromosomes (Scott and Long 1980). The number of per cell chiasma in late diplotene or diakinesis among stallions was counted to 54.4 ‫ע‬ 1.8, which is comparable to that found in sheep (Chapman and Bruere 1977;Long 1978), but is higher than that in pig (Burt and Bell 1987), cattle, and goat (Logue 1977).…”
Section: Discussionmentioning
confidence: 74%